Precious Instructions, Sagacious Decrees and the conception of the history of the present dynasty among the people of the Song Dynasty—in the example of the conception of the "ancestors" among the scholar-officials of the Song Dynasty. - Xiaonan, Deng (Chinese Studies in History)
The conception of the history of the present dynasty (benchao shiguan) in Song China is a complex issue involving many facets at the time and exerting salient influence in later Song studies. This article is not to produce an all-inclusive exploration but examines this conception through the lens of Precious Instructions (Baoxun) and Sagacious Decrees (Shengzheng). These texts, compiled by Song scholar-officials, selectively recorded the words and deeds of founding emperors to shape the "ancestors" as ideal political models. The article argues that these works were not mere historical records but functioned as didactic tools for imperial education, particularly within the Jingyan (Colloquium) lectures. Through editorial choices—omitting scandals and emphasizing specific virtues—officials actively constructed a "way of the ancestors" (zuzong zhi fa) to guide contemporary governance and restrain imperial power. The study highlights a tension between historical fact and political narrative, noting that while modern research must critically peel back these layers of interpretation, the Song elite viewed this "reshaping" as a legitimate expression of collective political wisdom and moral cultivation rather than simple flattery.